Analysis Of Organizational Culture And Career Development On Organizational Commitment With Job Satisfaction As A Mediating Variable At The Large Plantation Seed And Plant Protection Center In Medan - Hayati, Rini; Ferine, Kiki Farida; Surya, Elfitra Desy (Universitas Dehasen Bengkulu, 2026)
Organizational commitment is an important factor in improving the effectiveness and success of government agencies in achieving strategic objectives. This study aims to analyze the influence of organizational culture and career development on organizational commitment with job satisfaction as a mediating variable at the Medan Plantation Seed and Protection Center (BBPPTP). The study uses a quantitative approach with a survey method. The research population consisted of all 135 civil servants (PNS) at BBPPTP Medan, all of whom were included in the sample. Data were collected through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS. The results showed that organizational culture and career development had a positive and significant effect on organizational commitment. Organizational culture also has a positive and significant effect on job satisfaction, while career development does not have a significant effect on job satisfaction. Job satisfaction has been proven to have a positive and significant effect on organizational commitment and mediates the influence of organizational culture on organizational commitment. However, job satisfaction does not mediate the influence of career development on organizational commitment. These findings indicate that strengthening positive organizational culture and increasing job satisfaction are key factors in building organizational commitment among BBPPTP Medan employees. This study is expected to provide empirical contributions to the development of human resource management in the public sector and serve as a basis for formulating strategic policies to increase employee commitment.